32‐3: Stability Enhancement of Light Emitting Diode Based on Quantum Dots through Atomic Layer Deposition. Issue 1 (2nd June 2017) - Lu, Rui; Chen, Wei; Chen, Yulong; Yang, Lei; Hao, Junjie; An, Na; Ma, Haoyue; Bian, Dun; Wu, Dan; Wang, Kai; Sun, Xiao Wei
Abstract : In this work, atomic layer deposition (ALD) technique has been used as an efficient method to improve the operational stability of quantum dots (QDs) optimized white light emitting diode (WLED), by depositing an alumina layer on the outer surface layer. The luminescent microspheres (LMS) were also employed as QDs composite which had been integrated with yellow phosphors on‐chip packed on blue LED to achieve white light with high color rendering.